REVITALISASI PENDIDIKAN DALAM ISLAM (TELAAH AYAT DAN HADIST TARBAWI) - Firdaus Ainul Yaqin (UNZAH Genggong, 2020)
The industrial era 4.0 gave birth to a breakthrough for human life, namely technology that is able to serve human life. Technology is expected to replace the role of humans so that effectiveness in doing things increases and minimizes human error. But the development of technology will not be able to completely replace the role of humans, including in the field of education. The education process still requires a process of active interaction between people. The education process is one of the objectives in the teachings of Islam because it is included in the endeavor of al-aql, that's why education occupies an important position in the teachings of Islam. There are many root words that have educational meanings including: tarbiyah, ta'lim, and ta'dzib. All of these words have educational meanings but have the characteristics of different approaches, ranging from biological or moral approaches. Education has the meaning of developing and nurturing the potential of every child so they can grow optimally. This is because education is associated with something that is growing, both physically and logically. That's why the educational process requires active dialogue and communication between educators and students. Islam places education not only as a means to achieve worldly success in the form of material wealth but education in Islam seeks to strike a balance between science in general and religious knowledge, while prioritizing Aqeedah as a foundation in building knowledge for human life. Some traditions even verses of the Qur'an clearly teach about the importance of science and the educational process. Humans will get glory both in the world and in the hereafter if they take education and gain knowledge. Islamic education is defined as an educational process that is sourced from al-Qur'an and al-Hadith. This educational model does not only prioritize reasoning but also instills aqidah in the heart which is expected to be able to be implemented in daily life in the form of morals al-karimah. Keyword: Education, Islam, verses and hadith tarbawi